Prevalence of Human Papillomavirus infection among Chilean women from 2012 to 2016. Issue 9 (28th March 2017) - Vergara, Nicolás; Espinoza, Gloria; Balanda, Monserrat; Quiero, Andrea; Hidalgo, Wilma; San Martín, Héctor; Ramírez, Alejandro; Ramírez, Eugenio
Abstract : Here, we evaluated the prevalence of Human Papillomavirus (HPV) in two groups of Chilean women. The first group consisted of 3235 women aged 18‐64 years attended in six primary care centers of Santiago. The second group consisted of 456 women 18‐85 aged who consulted the Gynaecology Department of the Reference Hospital of Santiago. Samples were collected from October 2012 to February 2016. Cervical swabs were analyzed both HPV genotyping by PCR and Reverse Line Blot, and cervical cytology by Pap testing. Results showed a prevalence of 12.0% HPV positive, 10.3% high‐risk (HR) HPV types positive, 3.9% low‐risk (LR) HPV types positive, and 1.0% Pap positive in group 1. The most frequent types were 16, 66, and 59, with a prevalence of 3.0%, 1.6%, and 1.5%, respectively. The prevalence were 71.9% HPV positive, 67.3% HR‐HPV types positive, 13.6% LR‐HPV types positive, and 62.5% Pap positive in group 2. The most frequent types were 16, 31, and 58, with prevalence of 33.6%, 10.5%, and 7.0%, respectively. Among infected women with HPV: 7.6% were infected with HPV16 or HPV18, 3.0% with HPV31, HPV33 or HPV45, and 6.7% with any other HR‐HPV. These findings show great difference in HPV prevalence and types between primary care and reference center, and provide useful epidemiological information to assess the impact of HPV vaccination in the future.